The first in vivo multiparametric comparison of different radiation exposure biomarkers in human blood - Tichy, Ales; Kabacik, Sylwia; O'Brien, Grainne; Pejchal, Jaroslav; Sinkorova, Zuzana; Kmochova, Adela; Sirak, Igor; Malkova, Andrea; Beltran, Caterina Gomila; Gonzalez, Juan Ramon; Grepl, Jakub; Majewski, Matthaeus; et al. (PLoS One, 2018)
The increasing risk of acute large-scale radiological/nuclear exposures of population underlines the necessity of developing new, rapid and high throughput biodosimetric tools for estimation of received dose and initial triage. We aimed to compare the induction and persistence of different radiation exposure biomarkers in human peripheral blood in vivo. Blood samples of patients with indicated radiotherapy (RT) undergoing partial body irradiation (PBI) were obtained soon before the first treatment and then after 24 h, 48 h, and 5 weeks; i.e. after 1, 2, and 25 fractionated RT procedures. We collected circulating peripheral blood from ten patients with tumor of endometrium (1.8 Gy per fraction) and eight patients with tumor of head and neck (2.0-2.121 Gy per fraction). Incidence of dicentrics and micronuclei was monitored as well as determination of apoptosis and the transcription level of selected radiation-responsive genes. Since mitochondrial DNA (mtDNA) has been reported to be a potential indicator of radiation damage in vitro, we also assessed mtDNA content and deletions by novel multiplex quantitative PCR. Cytogenetic data confirmed linear dose-dependent increase in dicentrics (p < 0.01) and micronuclei (p < 0.001) in peripheral blood mononuclear cells after PBI. Significant up-regulations of five previously identified transcriptional biomarkers of radiation exposure (PHPT1, CCNG1, CDKN1A, GADD45, and SESN1) were also found (p < 0.01). No statistical change in mtDNA deletion levels was detected; however, our data indicate that the total mtDNA content decreased with increasing number of RT fractions. Interestingly, the number of micronuclei appears to correlate with late radiation toxicity (r2 = 0.9025) in endometrial patients suggesting the possibility of predicting the severity of RT-related toxicity by monitoring this parameter. Overall, these data represent, to our best knowledge, the first study providing a multiparametric comparison of radiation biomarkers in human blood in vivo, which have potential for improving biological dosimetry.
Keywords: radioterapie; senioři nad 80 let; Endometrial Neoplasms; Humans; Micronuclei, Chromosome-Defective; lidé středního věku; Radiotherapy Dosage; mitochondriální DNA; nádory hlavy a krku; Aged, 80 and over; DNA, Mitochondrial; Middle Aged; Radiation Exposure; Transcription, Genetic; Leukocytes; celková dávka radioterapie; mužské pohlaví; chromozomální aberace; nádory endometria; radiační expozice; Chromosome Aberrations; mikrojádra chromozomálně defektní; biologické markery; ženské pohlaví; vztah dávky záření a odpovědi; lidé; Dose-Response Relationship, Radiation; Radiotherapy; Head and Neck Neoplasms; Biomarkers; Aged; Radiometry; senioři; leukocyty; Male; radiometrie; genetická transkripce; Female